The Escalada Formation: Characterization of a potential chert supply source in the Cantabrian Mountains (NW Spain) during prehistory. (Journal of Lithic Studies, 2016)
A study of the chert nodules found in the Escalada Formation (Carboniferous, Ponga region, Cantabrian Zone) was carried out as a means to characterise a number of lithic raw materials found in several prehistoric sites of the Cantabrian Mountains (NW Spain). This study comprises fieldwork aimed at locating the outcrops and obtaining samples. Some selected samples from two localities were used for both petrological (macroscopic and microscopic analyses from thin sections) and geochemical (X-ray fluorescence and powder diffraction) analysis. The macroscopic study shows a rather homogeneus coloration and a conchoidal fracture although two extreme types of cherts with a variety of intermediate forms can be differentiated according to the matrix composition. The microscopic analysis shows a high heterogeneity in carbonate versus silica percentage and gentle differences in some other features such as type of silica, origin of carbonates, occurrence of organic matter and type of skeletal components. The results of several geochemical analysis suggest that there are not geochemical features neither in the major elements nor in the traces that allows us to clearly distinguish between the analysed samples. All these studies allow us to define the main features of these chert nodules and to establish several types and varieties among them. Those varieties with high percentage of silica and with a more homogeneous matrix are the most suitable samples for knapping. These results together with the study of the geological and geographical location of archaeological sites suggest that the nodules from the Escalada Formation likely were lithic material supply sources used in knapping activitiesWhen aiming to demonstrate the use of these materials at archaeological sites the sole macroscopic analysis of the pieces does not suffice; further analyses, such as those involving thin sections, are necessary. The absence of chert from Escalada Formation in some Mesolithic sites in the area was confirmed via these additional analyses.